South Africa : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that South Africa's vulnerabilities have become more pronounced and are set to increase further unless economic growth revives. Following near-standstill in economic activity in 2016, growth is projected to increase to 1.0 percent in 2017 and 1.2 percent in 2018. The current account deficit is projected to decline to 3 percent of GDP in 2017, boosted by mining and agricultural exports. Consumer price inflation recently returned below 6 percent, owing in part to the easing of the drought, and is projected to remain marginally below the upper threshold of the 3-6 percent target band for the remainder of 2017 and in 2018.